Reliability of PCA LAI-2000 to indicate foliar nitrogen content in mature oil palm - Johari, Amiruddin (2015)
Oil palm is the golden crop of Malaysia, the vast production of palm oil have made Malaysia the second largest producer after Indonesia. Nitrogen (N) as the basic macronutrient serve as one of major fertilizers contributes to vegetative growth given appropriate manuring and fertilizing. Fronds growth of oil palm create canopy as the oil palm matured and canopy measurement can indicate vegetation growth. As N is responsible for vegetation growth, plant canopy in term of Leaf Area Index (LAI) that quantifies the amount of foliage area per unit ground surface area can be used as indirect method to asses foliar nitrogen. LAI, is therefore an important parameter controlling many biological and physical processes associated with vegetation on the Earth's surface, such as photosynthesis, respiration, transpiration, carbon and nutrient cycle, and rainfall interception. LAI is a required input to many climate and ecological models. This study conducted in United Malacca Berhad (UMB) plantation, the main objective of the study is to significantly identify the relationship of plant canopy (LAI) to foliar nitrogen content. Different N rates of 0, 1 and 2 kg/palm were applied on oil palm fields planted in 2002 and 2005. The parameters recorded were the LAI readings and foliar N content of the palm. For LAI measurement, PCA LAI-2000 was used to estimate LAI of oil palm. The relationship between foliar N content and LAI value of oil palm leaves were analyzed and the results showed weak relationship explaining these two parameters, where the linear regression illustrated the highest R2 value of 0.253. It is concluded that PCA LAI-2000 is not a reliable tool to estimate foliar N content via LAI or canopy cover consisted in mature oil palms in fields.